MONOPOLI DALAM PERSPEKTIF EKONOMI ISLAM - Dede Abdul Fatah (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
Monopoly in Islamic economic perspective means withholding or hoarding goods on purpose, especially in times of scarcity, with the goal of raising the price at a later date in order to obtain greater profits. Monopolistic practices is a type of violation will result in mu‘âmalah because market mechanisms disrupted,so that producers will get a big profit (monopolistic rent), while the consumer due to the accumulation of actions will suffer and get loss. Therefore, this monopoly will bring people in general harmed by the act of a small group of monopolists very unjust, selfish and irresponsible.DOI: 10.15408/aiq.v4i2.2546